(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
Food of animal origin is exposed to hazards of different kinds (bacteria, viruses, parasites or chemical substances), which can be transferred to consumers. Foodborne diseases caused by biological and chemical agents are a global public health problem.The COVID-19 pandemic and climate change increases the risks for foods safety of food animal origin, and consequently for animal, human and environmental health. Good livestock practices and Biosecurity are favorable for food safety, and food and nutrition security. The aim of this essay is share to information about food safety, sustainable development and climate change relevant to livestock systems.